Recent Advances in Electrochemically Mediated Reactions of Diselenides - Zhan, Lei; Wang, Qian; Tang, Hai-Tao; Mo, Zu-Yu; Pan, Ying-Ming (SynOpen, 2023)
Organoselenium compounds are crucial molecules that are utilized extensively in diverse fields such as medicine, agriculture, catalysis, and organic materials. The incorporation of selenium atoms into organic molecules holds significant importance in synthetic chemistry. Organic electrochemical synthesis, a green, mild, and efficient strategy, has displayed remarkable potential for organoselenium chemistry synthesis. Consequently, there has been substantial interest in recent years in researching electrochemically mediated synthesis of organoselenium compounds. This review provides an overview of the progress made in electrochemically mediated organic selenium reactions over the last decade, including electrochemical mediated selenium catalysis, electrochemical oxidation of diselenide coupling, and electrochemical oxidation tandem selenocyclization. The scope, limitations, and mechanisms of those reactions are emphasized.1 Introduction2 Electrochemical Selenium-Catalyzed Reactions3 Electrochemically Mediated Coupling of Aromatic/Heterocyclic Rings with Diselenides4 Electrochemically Mediated Tandem Selenocyclization5 Conclusion
Keywords: organic electrochemical synthesis; organoselenium compounds; selenium catalysis; diselenide coupling; tandem selenocyclization